ANALISIS STRATEGI FUNGSI PRODUKSI PADA UKM DAUN AGEL HANDICRAFT DI BANGKALAN - ISTIGFARINI, WENNY (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Small and Medium Enterprises (SMEs) have a strategic role in national economic development, in addition to the role in economic growth and employment also play a role in the distribution of development outcomes. One of them leaves Agel handicraft SMEs, small and medium businesses located in Bangkalan produces leaves agel fiber craft. The main problem seems to be lack of SME quality of their products and increased competition in the market. To stand in the market, it is necessary for SMEs to face the new challenges by adopting the right strategy. From the analysis conducted strtaegi there are two strategies that can be implemented by SMEs Leaves Agel Handicraft short-term strategies that can be implemented by SMEs are Leaves Agel Handicraft stretegi related diversification is to replace raw materials contained in the area, one of them by changing the raw material leaves agel with water hyacinth, pandanus leaves. The strategy for the medium term that can be run by SMEs Leaves Agel Handicraft is to expand the network of raw material suppliers that are outside Bangkalan. Key Words: Production Function Strategy, SWOT